1996
DOI: 10.1023/a:1016440707092
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This D-oligopeptide model series served as a useful probe for the structural requirements for paracellular absorption in vivo. A critical determinant of bioavailability is molecular size, expressed as molecular weight in this study; net charged appeared of much lesser importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Previous studies have indicated that d-peptides or d-proteins composed of d-amino acids are potential therapeutic agents with long half-lives in vivo and even oral bioavailability. [10] To find d-peptides that can bind to at arget protein of interest, the method of choice is mirror-image phage display. [10a, 11] In this technology,t he mirror image (a d-protein) of the natural ltarget protein is made by chemical synthesis.This d-protein is used to screen for binding of l-peptides displayed on phages.…”
mentioning
confidence: 99%
“…Previous studies have indicated that d-peptides or d-proteins composed of d-amino acids are potential therapeutic agents with long half-lives in vivo and even oral bioavailability. [10] To find d-peptides that can bind to at arget protein of interest, the method of choice is mirror-image phage display. [10a, 11] In this technology,t he mirror image (a d-protein) of the natural ltarget protein is made by chemical synthesis.This d-protein is used to screen for binding of l-peptides displayed on phages.…”
mentioning
confidence: 99%
“…[10] To find d-peptides that can bind to at arget protein of interest, the method of choice is mirror-image phage display. Previous studies have indicated that d-peptides or d-proteins composed of d-amino acids are potential therapeutic agents with long half-lives in vivo and even oral bioavailability.…”
mentioning
confidence: 99%
“…Certain physicochemical properties are typically predictive of the intrinsic cell membrane permeation of a molecule via the transcellular pathway. For instance, as the molecular surface area or polar surface area of a transcellular permeant increases, its cell membrane permeation will decrease. , In contrast, the relationship between cLogP and cell membrane permeation is nonlinear, i.e., the permeability decreases and plateaus at both low (e.g., negative) and high cLogP values…”
Section: Resultsmentioning
confidence: 99%